Pathogenesis of Haemorrhagic Septicaemia (HS) in cattle and buffalo: clinical signs, pathological changes, reisolation and detection of Pasteurella multocida using culture medium and Polymerase Chain Reaction (PCR - Priadi, Adin; Natalia, Lily (Indonesian Animal Sciences Society, 2000)
In the study of the pathogenesis of Haemorrhagic Septicaemia (HS), one cattle and one buffalo were infected subcutaneously with a dose of 4 x 108 colony forming units of Pasteurella multocida B:2 in the neck region. The post infection clinical findings were observed. During this observation period, bacterial isolation was carried out from heparinised blood and nasal swabs. The buffalo succumbed 2 hours earlier than the cattle.111e post mortem pathological changes in cattle and buffalo were similar but the lesions most severe in the buffalo. The prominent changes were observed in the lungs and bronchi of both animals. Bacterial reisolation and Polymerase Chain Reaction (PCR) for P. multocida were carried out trom various samples kept at room temperature without any preservative for 15, 35 and 59 hours after the death of the animals. After 59 hours, heavily contaminated samples were found in all organs except bone marrow. Reisolation of P. multocida trom these samples was difficult, however, the organism can still be identified by PCRTo improve the viability of Pasteurella multocida and reducing the growth of contaminants, transport medium containing selective antibiotics was developed. Amikacin and Gentamicin were good selective antibiotics to suppress other contaminating organisms. Â Key words: Pathogenesis, Pasteurella multocida B:2, cattle and buffalo, selective medium, PCR